2001
DOI: 10.1148/radiology.220.2.r01au34489
|View full text |Cite
|
Sign up to set email alerts
|

Celiac-Bimesenteric Trunk: Anatomic and Radiologic Description—Case Report

Abstract: The authors report the case of a 39-year-old man with a common origin of three arteries-the celiac, superior mesenteric, and inferior mesenteric arteries-that has not been described previously in the literature, to their knowledge. This variant, which they call the celiac-bimesenteric trunk, is documented with a selective angiogram, and an embryologic explanation is offered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 2 publications
1
25
0
2
Order By: Relevance
“…In humans, there is also the presence of a celiac-mesenteric trunk formed by celiac artery and the superior mesenteric artery (Çiçekcibaºi et al 2005). Still in humans, there is a rare incidence of a celiac-bimesenteric trunk formed by the celiac artery, superior mesenteric artery and inferior mesenteric artery (Bergman et al 1988, Nonent et al 2001. Schwarze (1970) and Nickel et al (1983) reported that the celiac artery arises at the level of the 17 th and 18 th thoracic vertebra in equines, at the level of the 1 st lumbar vertebra in bovines and carnivorous.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, there is also the presence of a celiac-mesenteric trunk formed by celiac artery and the superior mesenteric artery (Çiçekcibaºi et al 2005). Still in humans, there is a rare incidence of a celiac-bimesenteric trunk formed by the celiac artery, superior mesenteric artery and inferior mesenteric artery (Bergman et al 1988, Nonent et al 2001. Schwarze (1970) and Nickel et al (1983) reported that the celiac artery arises at the level of the 17 th and 18 th thoracic vertebra in equines, at the level of the 1 st lumbar vertebra in bovines and carnivorous.…”
Section: Discussionmentioning
confidence: 99%
“…Nayak (15) reported a common celiacomesentericophrenic trunk (CMPT). Moreover, Noment et al (16) reported a case in which all three arteries were converted into one trunk, namely the celiacobimesenteric trunk (CBMT). Koizumi et al described a case in which the dorsal pancreatic artery (DPA) originated from the CA (17).…”
Section: Introductionmentioning
confidence: 99%
“…Its branches namely left gastric (LGA), common hepatic (CHA) and splenic (SA) arteries supply the primary organs of the supracolic abdominal compartment namely the stomach, pancreas, spleen and liver (Charbon & Anderson, 1989). Reported variations in the branching pattern of the celiac trunk include absence of the trunk (Vandamme & Bonte, 1985), presence of collateral vessels (Cavdar et al, 1998) and anomalous branches (Cavdar et al, 1997;Nonent et al, 2001;Loukas & Jordan, 2006;Katagiri et al, 2007) and even bifurcation of the trunk (Ucerler & Asli, 2006). Such variations in the pattern of branching of the celiac trunk may predispose to iatrogenic injury during surgical procedures such as total pancreatomy (Vandamme & Bonte, 1990;Gielecki et al, 2005) and resection of tumors of head of pancreas (Lin, 2005).…”
Section: Introductionmentioning
confidence: 99%